Protection mechanisms: effective management of currency risk using derivatives - Pavlikova A. S. (Innovative approaches to management in economic, technical and legal systems, 2025)
the article discusses origin and types of currency risk, financial instruments for its mitigation for companies making payments in foreign national currency on international markets. The main derivative financial instruments for hedging risks, like forward and futures contracts, options, currency swaps and FRAs are considered. Special attention is paid to the use of such option strategies, like straddle and iron butterfly, allowing to lock potential losses.
Keywords: производные финансовые инструменты; hedging; валютные риски; хэджирование; опционные стратегии; currency risk; derivatives; option strategies